Digital whole slide imaging for pleural fluid cytopathology diagnosis: Accuracy, sensitivity, specificity, and concordance - Bannarakna, Raweewat; Waraasawapati, Sakda; Titipungul, Tanin; Chaisuriya, Nipon; Intarawichian, Piyapharom (Asia-Pacific Journal of Science and Technology, 2022)
Digital whole slide imaging (WSI) is a developing technique enabling digital pathology for research applications. This investigation aimed to determine the accuracy, sensitivity, specificity, and concordance of non-gynecological cytopathology specimen (pleural fluid) diagnoses made using WSI and glass slides. Sixty pleural fluid cytology specimens were prepared in glass slides and scanned with a digital slide scanner for WSI. Two pathologists interpreted both the glass and digital slides then the accuracy, sensitivity, specificity, and concordance (Kappa coefficient) of their diagnoses were examined between the techniques. A three-week interval separated the WSI and glass slide interpretations. The results found by pathologists 1 and 2 showed that the WSI accuracy were 91% and 93%, sensitivity was 89.3% and 86.7%, specificity was 92.3% and 100%, and concordance (Kappa coefficients) were 87% (0.74, p <0.001) and 95% (0.90, p< 0.001), respectively. Therefore, WSI has the potential to be applied in the diagnosis of pleural fluid cytology with accuracy, sensitivity, specificity, and concordances equal to standard diagnosis techniques. In the future, the flexibility, and utility, and other potential aspects of WSI will be widely used in research and routine cytopathological diagnosis.